DETERMINATION OF HEAVY METALS CONCENTRATION OF LOCAL AND IMPORTED WHEAT GRAINS STORAGE AND WHEAT FLOUR IN SOME SILOS of BAGHDAD CITY - Mahdi, R. S.; Omran, F. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The aim of this study was to estimate the levels of some toxic heavy metals such as (Cd, Pb,Cr,Ni,Zn,Cu,Fe,Co,As)by using the X-Ray fluorescence .in a total of forty-one samples of wheat grains which were (local, American, Australian, Canadian and mixing mills) samples collected randomly and seasonally from three silos in Baghdad ,also wheat flour collected from mills related to the manufactured of grains of each silo. The results showed that the levels of (Cadmium, Lead and Chromium) were surpassed the permissible safe limits according to FAO/WHO (2001).It was found that the highest concentration of cadmium detected in wheat flour in AL Dora silo for summer and spring seasons were 12.6mg/kg, as well as the high level of lead 1.021mg/kg detected in AL Dora silo in local wheat for winter and summer seasons and wheat flour for spring season, also in Australian wheat for spring season in Taji silo. Finally, the high value of chromium content was in wheat flour in Taji silo for spring season (4.686) mg/kg. Generally, analysis of these data shows significant effects (P≤0.05) of most samples analyzed for Cd >Pb >Fe >Zn >Cu >Ni >Cr >Co while AS show no significant difference in all samples.